Studying on high organic loading wastewater treatment ability in UASB reactor of sludge granular prepared from the mixture of chitosan with anaerobic sludge - Hoang , Thị Tuyết Nhung; Nguyen, Văn Sức (Journal of Technical Education Science, 2008)
Anaerobic sludge granular was prepared from the mixture of chitosan with anaerobic sludge in laboratory conditions. After treatment the piggery wastewater by UASB reactor using prepared sludge granular, the results shown that the characteristic factors in UASB process such as alkali, volatile fatty acid (VFA) are very stable although organic loading rate was changed (from 1.5kgCOD/m3 to 10 kg COD/m3 of wastewatein) in the treatment time. COD reducing efficient in wastewater was attained more than 85 %.